Publishing with Illustrator and Freehand - Bergsland, David (Onward Press/Thomson Learning, 2002)
Real projects demand real solutions and Publishing with Illustrator and FreeHand delivers both! It goes beyond traditional tutorials to address the real-world challenges faced by digital publishers on a daily basis while generating vector graphics and illustrations. Practical advice, tips, and techniques for working with both AdobeÂđ Illustrator and MacromediaÂđ FreeHand - the current industry leaders in PostScript Illustration - are presented in a highly engaging and often humorous style that fosters creativity, develops problem-solving skills, and vastly increases production speed. Its in-depth technical coverage is coupled with advice on using both software programs to solve practical problems such as making designs printable, applying graphics to a variety of technologies, budget constraints, tight deadlines, business ethics, and more! Covering up-to-date software changes, this book also includes a thoughtful discussion of the strengths and weaknesses of PostScript illustration as a digital printing and publishing format. When followed from start to finish, it serves as a complete study manual that expands the reader's digital publishing knowledge while guiding them to expert-level use of Illustrator and FreeHand when creating and manipulating images